2022
DOI: 10.1093/humupd/dmac025
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering trends in female reproduction: a systematic review

Abstract: BACKGROUND To provide the optimal milieu for implantation and fetal development, the female reproductive system must orchestrate uterine dynamics with the appropriate hormones produced by the ovaries. Mature oocytes may be fertilized in the fallopian tubes, and the resulting zygote is transported toward the uterus, where it can implant and continue developing. The cervix acts as a physical barrier to protect the fetus throughout pregnancy, and the vagina acts as a birth canal (involving uteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 350 publications
1
22
0
Order By: Relevance
“…Similarly, assisted reproductive techniques offer high standardized in vitro conditions to demonstrate the adverse impact of high-fat conditions on oocyte maturation and fertilization (IVM/IVF), as well as during embryo development. In addition, modern-engineered reproductive culture systems [ 246 , 247 , 248 , 249 ] enable the increasingly physiological in vitro modelling of homeostasis, development, disease, and aging, thus offering novel cultural approaches to better interpret the multifactorial lifestyle impact on fertility. In this context, besides the increasing evidence that inflammation and ovarian aging are implicated in accelerating the decay of fertility, very little data clarify how obesity may further exacerbate these factors in compromising female reproductive health.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, assisted reproductive techniques offer high standardized in vitro conditions to demonstrate the adverse impact of high-fat conditions on oocyte maturation and fertilization (IVM/IVF), as well as during embryo development. In addition, modern-engineered reproductive culture systems [ 246 , 247 , 248 , 249 ] enable the increasingly physiological in vitro modelling of homeostasis, development, disease, and aging, thus offering novel cultural approaches to better interpret the multifactorial lifestyle impact on fertility. In this context, besides the increasing evidence that inflammation and ovarian aging are implicated in accelerating the decay of fertility, very little data clarify how obesity may further exacerbate these factors in compromising female reproductive health.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogels are by far the most prominently used bioengineering strategy for female reproductive medicine ( Francés-Herrero et al , 2022a ) and are composed of hydrophilic polymeric networks, which can deliver controlled drug-release into target wounds ( Narayanaswamy and Torchilin, 2019 ). Since ECM-based hydrogels are proven to mimic the physicochemical properties of the tissue of origin, we hypothesized they could provide the perfect environment for tissue regeneration ( Francés-Herrero et al , 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Recellularization of the decellularized endometrial tissue was conducted with human endometrial cells that showed functional phenotypic behavior by responding to a 28-day hormonal cycle that mimicked the human menstrual cycle [43]. This bioengineered explant culture may become an attractive in vitro model to better mimic in vivo physiological settings compared to standard 2D in vitro culturing systems to study processes in the human uterus, e.g., drugdose response, invasive cancer mechanisms, or implantation events, in particular if combined with organ-on a-chip strategies [4,11,44,45]. The organ-on-a-chip strategy utilizes a multi-channel microfluidic circuit system that connects several cell culture compartments containing cells of different phenotypes.…”
Section: Progress In Human Uterus Bioengineering With Decellularized ...mentioning
confidence: 99%
“…These principles achieved promising results in whole-organ bioengineering studies on rodents for non-reproductive organs [3,[5][6][7][8][9], but was also assessed for novel infertility treatment applications [10]. There are several promising scaffold types evaluated for uterus bioengineering applications which is extensively summarized in a recent systematic review [11]. These include scaffolds derived from different hydrogels [12][13][14], and scaffolds derived from biodegradable polyglycolic acid (PGA) and poly-dl-lactide-co-glycolide (PLGA) polymers [15].…”
Section: Introductionmentioning
confidence: 99%